1996
DOI: 10.1038/bjc.1996.54
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of P-glycoprotein 1 and 2 gene expression and protein activity in two MCF-7/Dox cell line subclones

Abstract: Summary The MCF-7 doxorubicin-resistant cell line MCF-7/Dox has been used extensively for studies of the multidrug resistance phenomenon. Using fluorescence-activated cell sorting (FACS), these cells were separated into two populations on the basis of rhodamine 123 (R123) accumulation. We designated these as low Pglycoprotein (LP-gp) and high P-gp (HP-gp)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…The results we obtained with ax-PKC confirm those of our previous report (increased expression in LoVo/C7 and LoVo/DX cells); a parallel decrease in e-PKC levels has also been observed in LoVo/C7 and LoVo/DX cells. Similar instances of inverse regulation of calcium-dependent and -independent PKC isoforms have been reported for human breast and cervix carcinoma cell lines and their multidrug-resistant variants, but it is not clear how this effect correlates with the resistant phenotype (Blobe et al, 1993;Drew et al, 1994;Davies et al, 1996). As to the substrates whose phosphorylation may be affected by these changes in PKC isoform pattern, no unequivocal indication has emerged from the various studies on this issue; P-gp has been shown to be phosphorylated by oc-PKC (Davies et al, 1996), but the impact of phosphorylation of P-gp on its activation is still a matter of debate.…”
Section: Discussionmentioning
confidence: 71%
“…The results we obtained with ax-PKC confirm those of our previous report (increased expression in LoVo/C7 and LoVo/DX cells); a parallel decrease in e-PKC levels has also been observed in LoVo/C7 and LoVo/DX cells. Similar instances of inverse regulation of calcium-dependent and -independent PKC isoforms have been reported for human breast and cervix carcinoma cell lines and their multidrug-resistant variants, but it is not clear how this effect correlates with the resistant phenotype (Blobe et al, 1993;Drew et al, 1994;Davies et al, 1996). As to the substrates whose phosphorylation may be affected by these changes in PKC isoform pattern, no unequivocal indication has emerged from the various studies on this issue; P-gp has been shown to be phosphorylated by oc-PKC (Davies et al, 1996), but the impact of phosphorylation of P-gp on its activation is still a matter of debate.…”
Section: Discussionmentioning
confidence: 71%
“…doxorubicin-. vinblastine-and colchicineresistant KB human epidermoid carcinoma cells (Davies et al 1996) and in KB-A 10 cell lines (Posada et al 1989b).…”
Section: Resultsmentioning
confidence: 99%
“…Mdr cells are characterized by an increased rate of both MDRJ transcription and gene amplification (Morrow et al, 1992;Madden et al, 1993;Davies et al, 1996). On level 20 weeks after drug removal, P-gp levels declined and, concomitantly, cells commenced to regain sensitivity towards doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…The following two conclusions help characterize the nature of the link between mdr and PKC: (1) the decrease in mdr phenotype and the restoration of the PKC expression pattern to that observed in wild-type cells are remarkably synchronous; (2) apart from PKC-a, PKC-0 may play a role in the maintenance of the mdr phenotype. Protein levels of both these isoenzymes are elevated in MCF-7/Adr compared with wild-type MCF-7 cells, whereas those of PKC-s are decreased (Blobe et al, 1993;Davies et al, 1996). PKC phosphorylates P-gp at three serine sites within the linker region of the P-gp molecule (Chambers et al, 1995).…”
Section: Discussionmentioning
confidence: 99%